Analysis of the formation of intermetallic compounds in foams Al-Cu-Ni obtained from recycled aluminum cans. (2019) - Torres, J. Torres; Valdés, A. Flores; Rivera, N.M. Trejo; Robles, J.M. Almanza
Abstract: Metal foams are characterized by having a low density, impact energy absorption, and properties of both sound and thermal insulation. In this paper, the use of recycled aluminum is proposed in order to produce foams at low cost, as it is much cheaper to recycle than to use pure metals. Aluminum alloys recycled, containing additional elements, precipitate second phase particles and intermetallic compounds during solidification, so that make all the properties and characteristics of the foams change drastically. So it is necessary to analyze the formation of intermetallic compounds in foams alloy Al-Cu-Ni from aluminum cans recycled